PENGARUH PEMBERIAN URINE MANUSIA DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI ( Oryza sativa L ) DITANAH REGOSOL - Teguh Teguh; Haryuni Haryuni; Muchlis Zainuri (JURNAL ILMIAH AGRINECA, 2018)
Human urine to supply at least 1% against the quantity of domestic waste water by 80 percent and 50 percent of the nitrogen phosphate. Rice production in Indonesia has not been sufficient for the needs of consumption pendududuk. This research aims to know the influence of the granting of human urine and manure NPK towards growth and yield of rice plants (Oryza sativa L) ditanah regosol. The research was carried out on april 29 to July 23, 2016 at the village, Sidomulyo Delanggu, Klaten sub-distrct with regosol soil types and elevations place 333 m above sea level. the study was performed using Randomyzead Completely Block DesignÂ  (RCBD) which consists of two treatment and repeated as much as 3 times repeats. With regard to the treatment of two factors, namely the granting of human urine dosage consists of 3 levels, namely: 0 ml/swath, 375 ml/swath, and 750 ml/swath named as A0, A1, and A2. Two factors i.e. dosing fertilizer NPK consists of 3 levels i.e. 0 grams/swath, 120 gram/swath, and 240 grams/swath named as the B0, B1, and B2. The results of the weight of dried grain per swath of rice low i.e. 624.33 grams/swath (7.8 ton/ha) in a combination treatment (A0B2) with human urine dosage 0 l/ha fertilizer NPK dosage and 300 kg/ha.The results showed: (1) treatment of human urine effect is real high against the plant, heavy wet grain perpetak grain dry weight per hide. (2) treatment of NPK real has no effect against all the parameters. (3) the combination of the influence of the grant between the human urine and manure NPK real has no effect against all the parameters. (4) the results of this research were obtained: wet grain Weight per plant swaths of padi's highest i.e. 827 grams/swath (10.3 tonnes/ha) in a combination treatment (A2B2) with a dosage of 1000 l/ha fertilizer NPK dosage and 300 kg/ha. The results of the weight of dried grain per swath of rice low i.e. 624.33 grams/swath (7.8 ton/ha) in a combination treatment (A0B2) with human urine dose 0 l/ha fertilizer NPK dosage and 300 kg/ha